Effects of lameness treatment for claw horn lesions on lying behaviour in dairy cows - Miguel-Pacheco, Giuliana G.; Thomas, Heather J.; Kaler, Jasmeet; Craigon, Jim; Huxley, Jonathan N. (Elsevier, 2016)
Lameness affects lying behaviour in dairy cattle, increasing total lying time and the number of lying bouts. However, there is limited information about the effect of lameness treatment on dairy cow behaviour. This study investigated the effect of four lameness treatments on lying behaviour (total lying time, number of bouts, average bout duration and laterality of lying) in dairy cows. Forty-four newly lame cows were treated randomly with one of four treatment protocols: trim only, trim + block, trim + NSAID, and trim + block + NSAID. Thirty-four non-lame control cows were matched by parity, days in milk, and farm-pen. Each cow had an accelerometer attached to the hind leg, lying behaviour data was collected over 5 days immediately after treatment and analysed using multilevel regression models.